Associations between demographics and clinical ideology, beliefs, and practice patterns: a secondary analysis of a survey of randomly sampled United States chiropractors - Zachary A. Cupler; Jordan A. Gliedt; Stephen M. Perle; Aaron A. Puhl; Michael J. Schneider (BMC, 2023)
Abstract Background The chiropractic profession in the United States (US) has a long history of intra-professional discourse surrounding ideology and beliefs. Large-scale efforts have evaluated 3 distinctive subgroups of US chiropractors focused on these areas of practice: spine/neuromusculoskeletal, primary care, and vertebral subluxation. To our knowledge, there have not been any prior studies exploring the factors associated with these ideology and belief characteristics of these subgroups. The purpose of this study was to explore, describe, and characterize the association of US chiropractors' ideology, beliefs, and practice patterns with: 1) chiropractic degree program of graduation, 2) years since completion of chiropractic degree, and 3) US geographic region of primary practice. Methods This was a secondary analysis of a cross-sectional survey of a random sample of US licensed chiropractors (n = 8975). A 10% random sample was extracted from each of the 50 states and District of Columbia chiropractic regulatory board lists. The survey was conducted between March 2018-January 2020. The survey instrument consisted of 7 items that were developed to elicit these differentiating ideologies, beliefs, and practice patterns: 1) clinical examination/assessment, 2) health conditions treated, 3) role of chiropractors in the healthcare system, 4) the impact of chiropractic adjustments [spinal manipulation] in treating patients with cancer, 5) vaccination attitudes, 6) detection of subluxation on x-ray, and 7) x-ray utilization rates. Multinomial regression was used to analyze associations between these 7 ideology and practice characteristic items from the survey (dependent variables) and the 3 demographic items listed above (independent variables). Results Data from 3538 respondents (74.6% male) were collected with an overall response rate of 39.4%. Patterns of responses to the 7 survey items for ideologies, beliefs, and practice characteristics were significantly different based on chiropractic degree program of graduation, years since completion of chiropractic degree, and geographic region of primary practice. Conclusions Among US chiropractors, chiropractic program of graduation, years since completion of chiropractic degree, and geographic region of primary practice are associated with variations in clinical ideology, beliefs, and practice patterns. The wide variation and inconsistent beliefs of US chiropractors could result in public confusion and impede interprofessional integration.